H.KREPKOGORSKI CESTODASÍ JABAYÍ SÚT EMIZIWShILER ENDOPARAZITI - Berdibaev, Abat Sultamuratovich; Abdurahmonov, Sherali Alisher ulı; Shayxova, Baxıtgúl Xabızovna; Urgenichbaev, Aybek Allambergen ulı (SCIENCE and SOCIETY, 2026)
Of the 156 specimens subjected to full and incomplete helminthological research, 56 specimens (35.2%) from wild mammals were infected with the H.krepkogorski cestode. Out of 56 individuals of the jackal C.aureus, 21 individuals (37.5%), 23 individuals of the wolf C.lupus, 5 individuals (21.7%), 42 individuals of the fox V.vulpes, 16 individuals (38.0%), and 38 individuals of the hare L.tolai, 14 individuals (36.8%) were infected with the H.krepkogorski tsestoda. In terms of the extensiveness of infection with the H.krepkogorski tsestoda, the highest level of infection was observed in foxes with V.vulpes at 38.0%, while in terms of infection intensity, the highest level of infection was observed in rabbits with L.tolai at 13–281 specimens.